1991
DOI: 10.1165/ajrcmb/5.6.539
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proliferation of Rat Lung Fibroblasts Induced by the Platelet-derived Growth Factor-AA, -AB, and -BB Isoforms Secreted by Rat Alveolar Macrophages

Abstract: Platelet-derived growth factor (PDGF)-like molecules secreted by alveolar macrophages have been postulated to be mediators of lung fibrogenesis since these cytokines stimulate the proliferation and chemotaxis of lung fibroblasts. We are studying the biology and biochemistry of rat macrophage-derived PDGF and have identified for the first time the specific isoforms of PDGF (-AA, -AB, and -BB) that these macrophages secreted in vitro following activation with either chrysotile asbestos or carbonyl iron spheres. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 32 publications
5
59
0
Order By: Relevance
“…Asbestos fibers also stimulate the secretion of PDGF isoforms and TGF-␣ in vitro and in vivo in rodent models. 10,12,30 Due to the potent mitogenic effect of these growth factors, these studies suggest a role for PDGF and EGF receptor ligands in causing a fibrotic response. However, they do not clearly establish a link between PDGF-or EGF-mediated cell proliferation and the subsequent deposition of collagen, which defines the fibrotic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Asbestos fibers also stimulate the secretion of PDGF isoforms and TGF-␣ in vitro and in vivo in rodent models. 10,12,30 Due to the potent mitogenic effect of these growth factors, these studies suggest a role for PDGF and EGF receptor ligands in causing a fibrotic response. However, they do not clearly establish a link between PDGF-or EGF-mediated cell proliferation and the subsequent deposition of collagen, which defines the fibrotic lesion.…”
Section: Discussionmentioning
confidence: 99%
“…PDGFR-a, but not PDGFR-P, mRNA, and peptide are upregulated at the site of asbestos-induced fibrotic lesions (23 (134). Furthermore, asbestos fibers induce proliferation of rat lung fibroblasts in serumfree media through a PDGF-dependent pathway that involves the PDGF-AA isoform and upregulation of the PDGF-a receptor (21,22).…”
Section: Platelet-derived Growth Factormentioning
confidence: 98%
“…PDGFR-a expression is increased in rat lung through IL-1 (130). Rat AM secrete more PDGF (all three isoforms( following exposure to asbestos in vitro ( 134). Exposure of mineral dust to tracheal explants results in increased expression of PDGF-A and -B chain gene expression (131).…”
Section: Platelet-derived Growth Factormentioning
confidence: 99%
“…Human lung macrophages were shown in 1985 to produce PDGF (37), and in 1988 we demonstrated that rat lung macrophages secrete a similar molecule (38). This macrophage product was found to account for the majority of fibroblast proliferation induced by culture medium "conditioned" by macrophages in vitro (39). Thus, PDGF, including the macrophage-derived (MD) molecule, is a potent mesenchymal cell mitogen commonly found in cell secretions.…”
Section: Introductionmentioning
confidence: 88%
“…We have studied the specific high-affinity receptors for TGF-fl and PDGF on the putative target cells, i.e., the rat lung fibroblasts (39,41 In 1981 (46), we showed that the majority of inhaled chrysotile asbestos fibers which are small enough to pass through the terminal bronchioles is deposited at the first bifurcation of the alveolar ducts in rats. This was accomplished by exposing the animals for only 0.5 or 1 hr, sacrificing them within 4 min after cessation ofexposure, and then counting the fibers at their sites of initial deposition by use of scanning electron microscopy FIGURE 2.…”
Section: Introductionmentioning
confidence: 99%